2006
DOI: 10.1128/jcm.44.1.160-165.2006
|View full text |Cite
|
Sign up to set email alerts
|

Viridans Streptococci Isolated by Culture from Blood of Cancer Patients: Clinical and Microbiologic Analysis of 50 Cases

Abstract: Clinical and microbiologic studies of 50 cases of viridans streptococcal bacteremia in cancer patients were performed. The bacteria were identified to species level by sequencing analysis of the 16S rRNA gene. At least nine Streptococcus spp. were found, including S. mitis (25 strains, 50.0% of 50); currently unnamed Streptococcus spp. (11 strains); S. parasanguis (five strains); S. anginosus (three strains); S. salivarius (two strains); and one strain each of S. gordonii, S. sanguis, S. sobrinus, and S. vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 32 publications
4
77
1
3
Order By: Relevance
“…Eight patients had underlying chronic liver disease (5 with chronic hepatitis C and 1 each with primary sclerosing cholangitis, alcoholic liver disease, and cryptogenic cirrhosis); 1 patient had fulminant hepatic failure of unknown cause. The median Child-Turcotte-Pugh score of patients with chronic liver disease was 10 (range, 6-10), and the median Model for End-Stage Liver Disease score was 17 (range, [13][14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight patients had underlying chronic liver disease (5 with chronic hepatitis C and 1 each with primary sclerosing cholangitis, alcoholic liver disease, and cryptogenic cirrhosis); 1 patient had fulminant hepatic failure of unknown cause. The median Child-Turcotte-Pugh score of patients with chronic liver disease was 10 (range, 6-10), and the median Model for End-Stage Liver Disease score was 17 (range, [13][14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Han et al 17 reported that 92% of levofloxacin-resistant streptococci cases had either prophylaxis or treatment with one of the quinolones within a week of a positive culture. In another series, all isolates of VGS were susceptible to levofloxacin and moxifloxacin, and minimum inhibitory concentrations of fluoroquinolones did not differ in patients with or without norfloxacin prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of levofloxacin-resistant VGS infection following prophylaxis has been reported in neutropenic patients. 3,4 In the study of Gautam et al, 1 only 1 isolate from a patient receiving norfloxacin was resistant to levofloxacin. However, primary prophylaxis is likely to be increasingly given to patients awaiting liver transplantation because it has been recently shown to improve survival.…”
Section: To the Editorsmentioning
confidence: 99%
“…S. mutans is the main causative agent of human dental caries, one of the most common infectious diseases afflicting humans [10]. Infection by commensal and zoonotic streptococcal species occurs primarily in immunocompromised individuals and the elderly [11][12][13][14][15]. Commensal organisms colonizing the oral mucosa, the surface of teeth (organisms of the groups S. mitis, S. mutans, S. salivarius, S. anginosus) and other mucosal niches (S. anginosus group), may cause infective endocarditis and have also been associated with serious suppurative infections (Table 1) [10,[16][17][18][19].…”
Section: Introduction -Streptococcal Infection Of Humansmentioning
confidence: 99%